2011
DOI: 10.2118/137748-pa
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Decline Analysis for Fracture-Dominated Shale Reservoirs

Abstract: Traditional decline methods such as Arps' rate/time relations and their variations do not work for wells producing from supertight or shale reservoirs in which fracture flow is dominant. Most of the production data from these wells exhibit fracture-dominated flow regimes and rarely reach late-time flow regimes, even over several years of production. Without the presence of pseudoradial and boundary-dominated flows (BDFs), neither matrix permeability nor drainage area can be established. This indicates that mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(104 citation statements)
references
References 25 publications
0
103
0
1
Order By: Relevance
“…Such as the Stretched Exponential (SE) decline model [19], the Power Law (PL) model [16], and Duong's model [20].…”
Section: Decline Curve Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such as the Stretched Exponential (SE) decline model [19], the Power Law (PL) model [16], and Duong's model [20].…”
Section: Decline Curve Modelsmentioning
confidence: 99%
“…In the stretched exponential method, q i , D i , and n are undetermined parameters; τ is equivalent to (n/D i ) 1/n [20].…”
Section: Propertiesmentioning
confidence: 99%
“…Ilk (2010), after analyzing production (rate) data from shale gas wells, developed a power-law model and a method of applying the model that arbitrarily switched from the power-law decline behavior to an exponential decline behavior. Duong (2011) also observed that a loglog plot of q/N p versus time was a straight line. Based on this observation, he developed a power-law type model and a procedure for its application.…”
Section: Introductionmentioning
confidence: 81%
“…As the importance of shale gas has increased over the last decade new methods have been proposed to model the behavior exhibited by long horizontal wells with multistage hydraulic fractures in shale reservoirs. These methods include, but are not limited to, the Stretched Exponential (SE) model [25,26], the Power Law model [24], and Duong's model [27]. Two decline curve analysis models are used in the study -the Arps Hyperbolic model and the Stretched Exponential model.…”
Section: Decline Curve Modelsmentioning
confidence: 99%